Corrosion and Strength Behaviors in Prestressed Tendon under Various Tensile Stress and Impressed Current Conditions - Ismail, Mohamed (Hindawi Publishing Corporation, 2017)
Corrosion occurs more rapidly under high tensile stress and this leads to several problems like degradation of serviceability and structural performance in PSC (prestressed concrete) structures. In this paper, impressed current method, so-called ICM, was applied to tendons under tensile loadings of 0.0, 20.0, 40.0, and 60.0% of ultimate load. With induction of 20 volts for 24 hours to tendon under tensile stress, loading was induced to failure and the ultimate load was evaluated with varying corrosion behaviors. The changing mechanical behaviors in the same corrosive conditions were evaluated under different initial prestressing levels. With increasing initial prestressing load, corrosion occurred more rapidly and corrosion amount also increased linearly. The ultimate load accordingly decreased with increasing initial prestressing and corrosion amount. The relationships between prestressing levels and corrosion behaviors were quantitatively obtained through regression analysis. The measured current during applied voltage and the related corrosion amounts were also dealt with in this work.